The Effect of Using Facebook on Student Learning Outcomes in Integrated Social Studies Subjects - Baruadi, Irvan E.; Panigoro, Meyko; Bahsoan, Agil (Journal of Economics Education and Entrepreneurship, 2023)
The development of social media makes performance faster, more precise and accurate so that it can improve learning outcomes. The social media that is often used nowadays is Facebook. A person's learning outcomes can be seen from the level of success in studying subject matter which is expressed in the form of grades or report cards for each field of study after experiencing the teaching and learning process. In the national education system, the formulation of educational goals, both curricular goals and instructional goals. The aim of this research is to determine the effect of using Facebook on student learning outcomes in integrated social studies subjects at SMP Negeri 2 Satap Biluhu. This research uses a quantitative approach, using survey research methods. The data used is primary data obtained from distributing questionnaires to students at SMP Negeri 2 Satap Biluhu. WhereasThe population in this study was all 69 students at SMP Negeri 2 Satap Biluhu. The sample for this study was taken from the entire population, namely 69 people.The data analysis technique uses simple linear regression.The results of the research show that there is an influence of using Facebook on student learning outcomes in the eyesIntegrated Social Sciences Lessons at SMP Negeri 2 Satap Biluhu. The magnitude of the influence of Facebook use on student learning outcomes is 31.6%.